Fikih Toleransi di Pesantren dalam Perspektif Sosiologi Hukum Islam - Abdul Ghoni (JURNAL INDO-ISLAMIKA, 2015)
This study is conducted in order to analyze the fiqh of tolerance in traditional and modern pesantren. This study is a kind of Islamic sociology of law which analyzes empirically how the response of community toward the value of tolerance. This study uses quantitative method in order to know the level of tolerance of five pesantren in Java. Those pesantren are Darunnajah Pesantren in Jakarta (1961), Rafah Pesantren in Bogor (1997), Ibnu Abbas Pesantren in Klaten (2007) which represent modern pesantren and Babussalam Pesantren in Bandung (1981), Al-Ishlah Pesantren in Kediri (1954) which represent traditional pesantren. The result of this study indicates that the traditional pesantren is better than the modern pesantren on the level of external tolerance, while the modern pesantren is better than the traditional pesantren on the level of internal tolerance.